Evaluating the Transformative Impact of Online Education on Medical Student Learning Outcomes [Letter] - Benhissoune A; Abdulqadir A; Shah H (Advances in Medical Education and Practice)
Abir Benhissoune,1 Anas Abdulqadir,2 Halia Shah3 1Keele University, Keele Medical School, Newcastle-under-Lyme, UK; 2University of Birmingham, Birmingham, UK; 3St George’s, University of LondonCorrespondence: Halia Shah, Email haliashah45@gmail.com